Educational and Religious Institutions and Their Role in Reducing Domestic Violence - Al-Zgair, Dr. Rehab Hussein Jabbar Ibrahim Al-Zgair (Sulaimani Journal for Humanities, 2026)
It is well-known to observers that violence has profound impacts on the lives of individuals, communities, and nations. Domestic violence, in particular, is a serious phenomenon that threatens human life. Although it is an old issue, its forms and manifestations have evolved over time. Domestic violence may be individual or collective in nature, and it is characterized as aggressive behavior involving the use of force or threats with the intent to cause physical or psychological harm or to destroy property. Among the most significant factors contributing to domestic violence are weak religious values, misinterpretation of religious or cultural norms, poor upbringing, and being raised in violent environments under difficult socioeconomic conditions such as poverty and unemployment. This study aims to examine the reality of domestic violence—a serious social challenge that has intensified in recent years—and calls for a comprehensive, multidimensional analysis of the issue. This phenomenon is growing both quantitatively and qualitatively and has increasingly infiltrated educational and religious institutions. There is a noticeable rise in violent behavior, riots, and criminal acts within schools and universities, as well as manifestations of violence in religious discourse. These are all indicators of the widespread prevalence of violence in society, posing a threat to social harmony, psychological well-being, and community peace. Violence in society manifests in many forms, beginning with verbal abuse, such as the use of offensive language, raised voices, and harsh tones in public spaces, social media, or even within meetings in governmental or private institutions. It continues with physical violence, including rough interactions, physical altercations, and the use of weapons—covering all aspects of criminal behavior. Furthermore, it extends to emotional and systemic violence such as indifference, apathy, laziness, obstruction of public services, and silence or passivity in the face of wrongdoing. This paper addresses the phenomenon of domestic violence and examines the role that educational and religious institutions play in curbing its spread. Special focus is given to understanding the deep-rooted causes of this phenomenon by clarifying the definition of domestic violence, its relationship with other concepts, identifying its various forms and causes, and analyzing how institutions can contribute to reducing it.
Keywords: Educational Institutions; Religious Institutions; Role in Reducing Domestic Violence